Financial Literacy and Saving Behavior Among Primary School Teachers: A Case Study of Primary Schools in Ssumbwe Village. - Edith Namanda (Uganda Christian University, 2026)
This research study examined the relationship between financial literacy and saving behavior among primary school teachers in Ssumbwe village. The constructs of the independent variable were financial knowledge, financial attitude and financial self-control while the constructs of the dependent variable were investment, consumption and saving culture. The study employed a descriptive and cross-sectional research design, and the data was collected using structured questionnaires which were administered to the primary school teachers. There was a 100% response rate, receiving a total of 80 responses which were analyzed using descriptive statistics, linear regression and Spearman’s correlation. The findings of this study revealed that primary school teachers exhibited moderate levels of financial literacy and saving behavior. Regression analysis further showed that 45.4% variation in saving behavior among primary school teachers happens as a result of financial literacy. The study concluded that financial literacy positively influences saving behavior and recommendations were made to policy makers to incorporate financial literacy programs in teachers’ academic schedule in order to provide primary school teachers with more insights on proper financial management.
Undergraduate